A Study of Heat Transfer of Concrete and Green Space Affected to the Building in Summer - Sangthongtong, Arissaman; Aungkosachanawanich, Atichart (Frontiers in Engineering Innovation Research, 2022)
The objective of this study is to study Heat Transfer of concrete and greenfield that affected to the building in summer by record the temperature in each thickness of the two surfaces at depth levels of -15.00 cm, -7.50 cm and 0.00 cm respectively, for ambient temperature is recorded every 1 minute, 24 hours a day, for 7 days under the suburbs area conditions, where without any tall buildings, there are only about the same size of buildings of the 30% surface around the building from the total area 100% on a sunny day. The data of temperatures at different depths of the same surface and the same depth at the different surface during the day and night for explain the heat transfer by using the diffusion equation to analyze the temperature occurring in the building. This research results that vertical heat transfer in different areas was affected incomplete transfer temperature due to there is blocking of heat transfer to the next layer. For this reason, the horizon heat transfer to the same areas is better than transfer to the building. So, the building floor that are surrounded by greenfield has less heat accumulation than the building floor that are surrounded by concrete. Therefore, in the summer, the concrete floors surrounding the buildings show accumulate heat level higher than the green space, both of during the day and night.